2019
DOI: 10.2337/dc19-1074
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes and Risk for Cardiovascular Disease by Hypertension Status in Black Adults: The Jackson Heart Study

Abstract: Recent studies have suggested that prediabetes is associated with an increased risk for cardiovascular disease (CVD) only among individuals with concomitant hypertension. RESEARCH DESIGN AND METHODS We analyzed the association between prediabetes and CVD by hypertension status among 3,313 black adults in the Jackson Heart Study (JHS) without diabetes or a history of CVD at baseline (2000-2004). Prediabetes was defined as fasting plasma glucose between 100 and 125 mg/dL or hemoglobin A 1c between 5.7 and 6.4% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The studies included in the previous meta-analysis were from the general population, so the health risk for prediabetes in patients with established atherosclerotic cardiovascular disease was not established. In recent years, many studies exploring the associations between prediabetes and the risk of cardiovascular disease and mortality have been published 7891011121314. On their own, most of the studies had limited power to draw solid conclusions, however, and their results have been debated.…”
Section: Introductionmentioning
confidence: 99%
“…The studies included in the previous meta-analysis were from the general population, so the health risk for prediabetes in patients with established atherosclerotic cardiovascular disease was not established. In recent years, many studies exploring the associations between prediabetes and the risk of cardiovascular disease and mortality have been published 7891011121314. On their own, most of the studies had limited power to draw solid conclusions, however, and their results have been debated.…”
Section: Introductionmentioning
confidence: 99%
“…5 Department of Statistics, Pontifícia Universidad Católica de Chile, Santiago, Chile. 6 Framingham Heart Study, Framingham, USA. 7 Department of Biostatistics, Boston University, Boston, USA.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between prediabetic dysglycaemia and other associated risk factors has been studied across the world [1,6,7], but there is no consensus, since each population has particularities regarding environmental, genetic and clinical factors involved. The identification of the most important conditions related to the incidence of prediabetic dysglycaemia is needed to allow the development of specific strategies to prevent the modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with established hypertension and diabetes mellitus (DM) have a 4-fold increased risk for the development of cardiovascular diseases (CVD) and substantially higher risk of CVD death and all-cause mortality. 1,2 Whether prediabetes (Pre-DM) alone is associated with adverse cardiovascular outcomes remains uncertain, 3,4 but findings from several longitudinal studies and meta-analyses have suggested that patients with Pre-DM have 3-12 times higher risk of incident DM than in the general population. [5][6][7][8] Besides, with the combination of hypertension, Pre-DM could accelerate the development of DM and further significantly increase CVD risk.…”
Section: Introductionmentioning
confidence: 99%